Metric Pattern Cutting for Children's Wear and Babywear - Alich, Winifred (Hoboken, N.J. : Wiley, 2013)
This fourth edition of iMetric Pattern Cutting for Children's Wear and Babywear/i remains the standard text book but has three majorimprovements. First, the sections have been re-organised to reflect changes in producing and marketing children's clothes. Today's popularity of easy-fitting styles and knitted fabrics means that basic i'flat' pattern/i icutting/i is used to construct the majority of children's wear and babywear and this type of cutting is therefore emphasised in this new edition. Shaped blocks and garments, cut to fit the body form, are still included, and are placed in chapters covering some school uniform garments or more expensive fashion or formal clothes. The book now clearly separates the sections useful to student beginners (Parts One, Two and Three), and also offers more advanced or specialist sections for students who wish to pursue a career in children's wear or for designers working in the different manufacturing sectors of the trade. The second change in this fourth edition is the introduction of colour coding to the sections; this makes it easier to identify specific processes in the book and enhances the illustrations. Finally, the size charts have been revised to reflect the changes in body sizing. The clear division of the boys' and girls' measurements in the charts has been in response to the way clothes are marketed and to co-ordinate with European size charts. 'Plus' charts for heavier children have also been added.
Title from resource description page (Recorded Books, viewed November 21, 2013).
"EBSCO evaluates our products based on the Web Content Accessibility Guidelines (WCAG) and the related Section 508 and EN 301 549 regulations in the US and EU. Most EBSCO products are substantially conformant with WCAG 2.2 level AA." Source: https://connect.ebsco.com/s/article/EBSCO-VPATs?language=en_US. Last accessed April 22, 2025.
WorldCat record variable field(s) change: 650
Keywords: Design; Industrial design; design (discipline); industrial design; DESIGN -- Fashion; FAMILY & RELATIONSHIPS -- General; Electronic books